Generalized anti fuzzy Lie algebras - Akram, Muhammad,; Chen, Wenjuan, (Utilitas Mathematica, 2012)
Using the concept of anti fuzzy points and its besideness to and non-quasi-coincident with a fuzzy set, we introduce generalized anti fuzzy Lie subalgebras, namely, (≺,≺ ∨ Υ m) *-fuzzy Lie subalgebras and present some of their properties. We introduce generalized anti fuzzy Lie subalgebras with thresholds. We also discuss the implication-based generalized anti fuzzy Lie subalgebras.